Scientific progress of fiscal transparency research at national governments level - Rodrigo Silva Diniz Leroy; Alejandro Saez-Martín; María del Carmen Caba-Pérez; Lucimar Antônio Cabral de Ávila (Revista de Contabilidad: Spanish Accounting Review, 2022)
This paper analyzes the scientific progress of research on fiscal transparency of national governments over the past 20 years. We explored the inherent and content characteristics of the papers, through a scientometric analysis, and investigated the role of externalities in the general progress and impact of the research. The number of impactful papers published on this topic can be considered low and we noted the predominance quantitative studies using external database, predominantly written by American and Spanish authors. About the role of language on the topic, English-speaking authors published earlier and have the most impactful papers. Also, the increase of papers is correlated with the regulations of Freedom of Information worldwide, although a low number of papers have specifically analyzed these acts. Finally, the rise of Open Budget Index data increased the number of papers published, though with less scientific impact. Considering the relevance of the topic, we propose future research niches to the literature on fiscal transparency, with different research types and alternative approaches, such as using primary data collection, qualitative and critical methodologies, in-depth case studies on the internal situation of unexplored countries, and studies focused on developing countries, mainly from Africa, Asia and Latin America.